Study on the Leakage Diagnosis of a Chilled Water Pipeline Network System Based on Pressure Variation Rate Analysis for Climate Change Mitigation - Xuan Zhou; Fei Liu; Lisheng Luo; Shiman Peng; Junlong Xie (Buildings)
In the context of increasing climate variability and extreme weather, chilled water systems face mounting challenges due to amplified heating and cooling demands and prevalent pipe leakages. Such leakages reduce system lifespan, raise maintenance costs, and degrade operational efficiency. To overcome the limitations of current methods, such as insufficient interpretability and computational complexity in leak localization, this paper proposes a novel leakage diagnosis and localization scheme based on pressure variation rate analysis in closed chilled water pipeline networks. Hydraulic models under both normal and leakage conditions are established and experimentally validated. Work conditions under various leakage points and flow rates were simulated, and the results reveal that pressure variation rates systematically increase with the leakage flow rate and vary with the distance from the leakage point. Specifically, when a leakage flow rate reaches 20% of the total rated flow, the pressure variation rate is 12.27% at the water supply side of the leaking branch and 20.27% at the return side. Furthermore, other monitoring points can be categorized into three distinct levels with variation rates ranging from approximately 3.36% to 19.65%. Overall, as the leakage flow increases from 2% to 20% of the design flow, the maximum pressure variation rate rises from 0.411% to 20.27%. A threshold of 3% for this novel leakage diagnosis and localization scheme is used for prompt leakage detection. This scheme not only enhances leak localization accuracy but also contributes to more efficient and reliable system operation under the pressure imposed by climate change.